Barriers and facilitators to developing faith-based peer interventions in Islamic religious settings for obesity prevention in women: A qualitative exploratory study - Maha Shafique; Salman Waqar; Sundus Mahdi (PLoS ONE, 2026)
Background Muslims represent the second-largest religious group in England and are geographically concentrated in socioeconomically deprived areas, predisposing them to health disparities. Faith-based interventions in Muslim communities are under-researched, despite their potential to promote health among hard-to-reach groups. This study investigated the barriers and facilitators to developing faith-based peer interventions aimed at reducing obesity-related health inequalities among South Asian Muslim women. Methods Using a qualitative approach, the study involved semi-structured interviews with nine Muslim women and six religious leaders of South Asian heritage, in Walsall, England. Interviews explored women’s health beliefs, the community milieu, attitudes towards faith-based health interventions and experiences of health-related activities in religious settings. The data was analysed thematically, which guided the development of a logic model for potential faith-based interventions. Results Socio-cultural factors may shape women’s health behaviours, gender constructs, the organisational dynamics of religious settings, and women’s involvement therein. All participants supported the integration of faith-based elements into future health interventions. While most participants favoured peer-led approaches, some recommended holistic health education by health professionals and religious leaders. Proposed peer strategies for prospective interventions included support and social groups, educational workshops, counselling, and group physical activities. Effective interventions require dynamic leadership, organisational partnerships, stable funding, and volunteer training. Friendliness, trustworthiness, competency, and positive role modelling were highlighted as desirable peer characteristics. Conclusion Faith-based peer interventions could serve as a culturally and religiously sensitive approach to address obesity-related inequalities in this demographic. Peer-based approaches enhance community engagement, social networks, and self-efficacy, potentially influencing socio-cultural norms. The success of future interventions would depend on co-production, reorganising religious spaces as community hubs, fostering inclusivity, and encouraging female leadership.